The role of the autonomic nervous system in the patterns of heart rate fragmentation. (May 2021) - Silva, Thaís Marques da; Silva, Carlos Alberto Aguiar; Salgado, Helio Cesar; Fazan, Rubens; Silva, Luiz Eduardo Virgilio
Highlights: Heart rate fragmentation (HRF) is a recent method for studying cardiac dynamics. Although related to adverse conditions, the origins of HRF are still unknown. We showed that sympathetic and vagal control contribute to decrease HRF. The amount of HRF is not correlated with most used heart rate variability indices. Abstract: Although rapid oscillations in heart rate (HR) are commonly attributed to vagal modulation of the heart, an ultra-rapid pattern of HR variation has recently been studied and named heart rate fragmentation (HRF). Objective: Considering that the underlying mechanisms of HRF are unknown, this study aims to evaluate the influence of the autonomic nervous system on HRF in rats. Methods: Electrocardiogram recordings were performed in awake rats at baseline conditions and after selective or combined pharmacological autonomic blockade. Series of RR intervals were calculated and HRF indices were computed, namely percentage of inflection points (PIP), percentage of patterns with zero (W0 ), one (W1 ), two (W2 ) or three (W3 ) inflection points, and percentage of patterns with only hard (W H ), soft (W S ) or mixed (W M ) inflection points. Moreover, the correlations between HRF indices and several important heart rate variability (HRV) indices were estimated. Results: PIP and W3 increased while W1 decreased after autonomic blockade (sympathetic, parasympathetic or combined). In contrast, the parasympathetic blockade noticeably decreased hard (W H ) and increased soft (W S ) HR transitions. Except for W0, HRF patterns grouped by the number of inflection points were not correlated to any studied HRV index. In contrast, patterns grouped by the type of inflection points are highly correlated to magnitude-dependent HRV indices. Conclusion: Cardiac sympathetic and parasympathetic influences similarly decrease HRF, while the parasympathetic control markedly increases the hard HR inflection points. Further studies should be conducted to verify whether the autonomic nervous system plays a different role in diseases marked by autonomic imbalance.